Worldwide trends in the prevalence of asthma symptoms: phase III of the International Study of Asthma and Allergies in Childhood (ISAAC). - Pearce,N; Aït-Khaled,N; Beasley,R; Mallol,J; Keil,U; Mitchell,E; Robertson,C; ISAAC,Phase Three Study Group (Thorax, 2007)
BACKGROUND: Phase I of the International Study of Asthma and Allergies in Childhood (ISAAC) was designed to allow worldwide comparisons of the prevalence of asthma symptoms. In phase III the phase I survey was repeated in order to assess changes over time. METHODS: The phase I survey was repeated after an interval of 5-10 years in 106 centres in 56 countries in children aged 13-14 years (n = 304,679) and in 66 centres in 37 countries in children aged 6-7 years (n = 193,404). RESULTS: The mean symptom prevalence of current wheeze in the last 12 months changed slightly from 13.2% to 13.7% in the 13-14 year age group (mean increase of 0.06% per year) and from 11.1% to 11.6% in the 6-7 year age group (mean increase of 0.13% per year). There was also little change in the mean symptom prevalence of severe asthma or the symptom prevalence measured with the asthma video questionnaire. However, the time trends in asthma symptom prevalence showed different regional patterns. In Western Europe, current wheeze decreased by 0.07% per year in children aged 13-14 years but increased by 0.20% per year in children aged 6-7 years. The corresponding findings per year for the other regions in children aged 13-14 years and 6-7 years, respectively, were: Oceania (-0.39% and -0.21%); Latin America (+0.32% and +0.07%); Northern and Eastern Europe (+0.26% and +0.05%); Africa (+0.16% and +0.10%); North America (+0.12% and +0.32%); Eastern Mediterranean (-0.10% and +0.79%); Asia-Pacific (+0.07% and -0.06%); and the Indian subcontinent (+0.02% and +0.06%). There was a particularly marked reduction in current asthma symptom prevalence in English language countries (-0.51% and -0.09%). Similar patterns were observed for symptoms of severe asthma. However, the percentage of children reported to have had asthma at some time in their lives increased by 0.28% per year in the 13-14 year age group and by 0.18% per year in the 6-7 year age group. CONCLUSIONS: These findings indicate that international